2012
DOI: 10.1016/j.devcel.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Diaphragms of Fenestrated Endothelia: Gatekeepers of Vascular Permeability and Blood Composition

Abstract: SUMMARY Fenestral and stomatal diaphragms are endothelial subcellular structures of unknown function that form on organelles implicated in vascular permeability: fenestrae, transendothelial channels and caveolae. PV1 protein is required for diaphragm formation in vitro. Here, we report that deletion of the PV1-encoding Plvap gene in mice results in the absence of diaphragms and decreased survival. Loss of diaphragms did not affect the fenestrae and transendothelial channels formation but disrupted the barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
241
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(253 citation statements)
references
References 52 publications
12
241
0
Order By: Relevance
“…2A). This result was verified with a second, independent endothelial cell marker, PLVAP (plasmalemmal vesicle-associated protein) (19) (Fig. 2B).…”
Section: Resultssupporting
confidence: 63%
“…2A). This result was verified with a second, independent endothelial cell marker, PLVAP (plasmalemmal vesicle-associated protein) (19) (Fig. 2B).…”
Section: Resultssupporting
confidence: 63%
“…Although it was previously reported that fenestrae density may contribute to the acute regulation of molecule entry into tissues due to their rapid turnover/appearance (3), no change in mean fenestrae diameter or density was detected. We cannot, however, exclude a role for alterations in the composition of fenestrae diaphragms, which act as size-selective molecular sieves involved in the regulation of basal permeability (42,43).…”
Section: Islet Blood Flow In Vivo Is Unchanged By Acute Increases In mentioning
confidence: 94%
“…1c) allow a facilitated diffusion into the stroma of molecules with molecular weight up to ~ 800 kDa (reviewed in [149]). The formation and maintenance of the fenestrations and their diaphragms involve the plasmalemma vesicle associated protein (Plvap) gene [143] and are under the control of the choroidal epithelium via a basolateral secretion of vascular endothelial growth factor (VEGF). Neutralizing choroidal VEGF production leads to strong morphological and functional alterations of the choroidal vasculature, with presumable consequences on CSF secretion and composition [86].…”
Section: Choroid Plexus Morphology In Relation To Blood-csf Exchangesmentioning
confidence: 99%